Representative variables of marketing and trading based innovation management model (2017)
This article aims to bond representative variables of marketing and trade activities as well as variables employed to structure and direct an innovation process to a management model. A general model that can be adapted to any industry in order to develop long term sustainability and economical well fair trough his impact product sells. This article presents variables in global context and innovations aspects. The investigation showed that the context variables that are held in control by the environment and are located into the core of the innovation management model exist as a primary feedback mechanism in order to establish an early review and properly readjust the organizations policy's, often translated in a mayor adjustment of operation process, such changes pursue disruptive innovations in order to adapt the product to a new consumption pattern in order to achieve company’s sustainability.